Wireless knee joint angle measurement system using gyroscope - Sudin, Sukhairi (2012)
Sensors are the eyes of control enabling one to see what is going on. Joint movement measurement system is a type of sensor to give the feedback measurement such angular displacement, angular velocity and angular acceleration. The measurements should be accurate and repeatability in order to get good controller’s performance. This project is concerned on the design and development of wireless joint movement measurement system specifically for Spinal Cord Injury (SCI) patient by using Functional Electrical Stimulation (FES) assisted activities such as cycling. FES is used to activate the paralyzed muscle by giving appropriate electrical signal through electrodes. Aims of this project are to create portable, wearable and wireless knee joint angle measurement system. To meet the desired aim if this project, practical and compact design technique are emphasized in order to create a wearable and usable product. The design of knee guard should be portable, flexible and at the same time comfortable while still giving a reasonably good grip to avoid misalignment of sensor after a few set of movement occur. Two gyroscope sensors are installed on the knee guard which covers thigh and shank part. Gyroscope provides the orientation of two axes and this orientation will determine the elevated position of thigh and shank. Technique of comparison of the position between thigh and shank, provided by both gyroscopes will generate angles at knee joint. This wireless based system will be helped to reduce the complexity of wired sensor as well as user-friendly and portable measuring system. Wireless communication using ZigBee protocol with two Xbee devices will be used to transfer data from the sensory unit to the computer controlled system. In sum, with using wireless based system, the movement limitation barrier is no longer an issue to the user. This device will be developed as a new measuring technique of joint angle and will be one of the contributing factors in Rehabilitation Engineering for patients with SCI.